Stainless Steel Parts Produced by Fused Deposition Modeling and a Sintering Process Compared to Components Manufactured in Selective Laser Melting - Moritzer, Elmar; Schumacher, Christian (Macromolecular Symposia)

Modeling of Stiffness Anisotropy in Simulation of Self-Piercing Riveted Components - Otroshi, Mortaza; Meschut, Gerson; Bielak, Christian Roman; Masendorf, Lukas; Esderts, Alfons (Key Engineering Materials)

Investigation and Realization of Watertight FDM Structures Made of Ultem 9085 in Pressurized Systems - Moritzer, Elmar; Elsner, Christian Lennart; Wächter, Julian; Knoop, Frederick (79th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Influence of material degradation on weld seam quality in hot gas butt welding of polyamides - Bialaschik, Max; Schöppner, Volker; Albrecht, Mirko; Gehde, Michael (Welding in the World)
The joining of plastics is required because component geometries are severely restricted in conventional manufacturing processes such as injection molding or extrusion. In addition to established processes such as hot plate welding, infrared welding, or vibration welding, hot gas butt welding is becoming more and more important industrially due to its advantages. The main benefits are the contactless heating process, the suitability for glass fiber reinforced, and high-temperature plastics as well as complex component geometries. However, various degradation phenomena can occur during the heating process used for economic reasons, due to the presence of oxygen in the air and to the high gas temperatures. In addition, the current patent situation suggests that welding with an oxidizing gas is not permissible depending on the material. On the other hand, however, there is experience from extrusion welding, with which long-term resistant weld seams can be produced using air. Investigations have shown that the same weld seam properties can be achieved with polypropylene using either air or nitrogen as the process gas. Experimental investigations have now been carried out on the suitability of different gases with regard to the weld seam quality when welding polyamides, which are generally regarded as more prone to oxidation. The results show that weld strengths are higher when nitrogen is used as process gas. However, equal weld strengths can be achieved with air and nitrogen when the material contains heat stabilizers.

Investigation of Metal‐Polymer Composites Manufactured by Fused Deposition Modeling with Regard to Process Parameters - Moritzer, Elmar; Elsner, Christian Lennart; Schumacher, Christian (Polymer Composites)

Fügen und Trennen von Kfz-Karosseriestrukturen in Leichtbauweise - Wibbeke, Tim Michael; Bartley, Auerélie; Chudalla, Nick; Meschut, Gerson (Fahrzeug + Karosserie und kfz-betrieb (Hrsg,); Tagungsband zu den Würzburger Karosserie- und Schadenstagen 22./23. Oktober 2021)

Clinching of Thermoplastic Composites and Metals—A Comparison of Three Novel Joining Technologies - Gröger, Benjamin; Troschitz, Juliane; Vorderbrüggen, Julian; Vogel, Christian; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Materials)

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, Benjamin; Köhler, Daniel; Vorderbrüggen, Julian; Troschitz, Juliane; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Production Engineering)
Abstract Recent developments in automotive and aircraft industry towards a multi-material design pose challenges for modern joining technologies due to different mechanical properties and material compositions of various materials such as composites and metals. Therefore, mechanical joining technologies like clinching are in the focus of current research activities. For multi-material joints of metals and thermoplastic composites thermally assisted clinching processes with advanced tool concepts are well developed. The material-specific properties of fibre-reinforced thermoplastics have a significant influence on the joining process and the resulting material structure in the joining zone. For this reason, it is important to investigate these influences in detail and to understand the phenomena occurring during the joining process. Additionally, this provides the basis for a validation of a numerical simulation of such joining processes. In this paper, the material structure in a joint resulting from a thermally assisted clinching process is investigated. The joining partners are an aluminium sheet and a thermoplastic composite (organo sheet). Using computed tomography enables a three-dimensional investigation that allows a detailed analysis of the phenomena in different joining stages and in the material structure of the finished joint. Consequently, this study provides a more detailed understanding of the material behavior of thermoplastic composites during thermally assisted clinching.

Measurement and Analysis of Residual Stresses and Warpage in Fiber Reinforced Plastic and Hybrid Components - Wu, Tao; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang; Niendorf, Thomas (Metals)
Glass/carbon fiber reinforced plastic (GFRP/CFRP) and hybrid components have attracted increasing attention in lightweight applications. However, residual stresses induced in the manufacturing process of these components can result in warpage and, eventually, negatively affect the mechanical performance of the composite structures. In the present work, GFRP, CFRP, GFRP/steel and CFRP/steel hybrid components were manufactured through the prepreg-press-technology always employing the same process parameters. The residual stresses of these components were measured through the hole drilling method (HDM), based on an adequate formalism to evaluate the residual stresses for orthotropic materials including the calculation of the calibration coefficients via finite element analysis (FEA). In FEA, the real material lay-up and mechanical properties of the samples were considered. The warpage induced by residual stresses was measured after the samples were removed from the tool. The measured residual stresses and warpage of four different types of samples were compared and results were analyzed in depth. The results obtained can be extended to other hybrid materials and even could be used for designing multi-stable laminates for application in adaptive structures. Moreover, the effects of the drilling process parameters of HDM, e.g., the drilling speed, the drilling increment and the zero-depth setting, on the resulting residual stresses of GFRP were investigated. The reliability of residual stress measurements in GFRP using HDM was validated through mechanical bending tests. The conclusions concerning the choice of optimal drilling parameters for GFRP could be directly applied for other types of samples considered in the present work.

The Effect of Fiber Waviness on the Residual Stress State and Its Prediction by the Hole Drilling Method in Fiber Metal Laminates: A Global-Local Finite Element Analysis - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Metals)

On the reliability of residual stress measurements in unidirectional carbon fibre reinforced epoxy composites - Magnier, A.; Wu, T.; Tinkloh, Steffen Rainer; Tröster, Thomas; Scholtes, B.; Niendorf, T. (Polymer Testing)

Entwurf netzfreundlicher Synchrongleichrichter mit integriertem Synchronwandler - Henkenius, Carsten

Measurement procedure for acoustic absorption and bulk viscosity of liquids - Claes, Leander; Chatwell, René Spencer; Baumhögger, Elmar; Hetkämper, Tim; Zeipert, Henning; Vrabec, Jadran; Henning, Bernd (Measurement)

Towards a Decision Support System for Cross-Sectoral Energy Distribution Network Planning - Kirchhoff, Jonas; Burmeister, Sascha Christian; Weskamp, Christoph; Engels, Gregor (Energy Informatics and Electro Mobility ICT)
Requirements for energy distribution networks are changing fast due to the growing share of renewable energy, increasing electrification, and novel consumer and asset technologies. Since uncertainties about future developments increase planning difficulty, flexibility potentials such as synergies between the electricity, gas, heat, and transport sector often remain unused. In this paper, we therefore present a novel module-based concept for a decision support system that helps distribution network planners to identify cross-sectoral synergies and to select optimal network assets such as transformers, cables, pipes, energy storage systems or energy conversion technology. The concept enables long-term transformation plans and supports distribution network planners in designing reliable, sustainable and cost-efficient distribution networks for future demands.

Revolten in Gelb und Grün. In 'Rosa und Hannah. Das Blatt wenden' inspiriert Joke J. Hermsen für Krisenzeiten - Lammer, Christina

Designing of thermosetting plastic components for direct screwing - Auslegung von Duroplastbauteilen zur Direktverschraubung - Moritzer, Elmar; Hillemeyer, Johannes; Kramer, M.; Hopmann, C. (Joining Plastics)

Characterization of wood-filled thermoplastic polyurethanes for the injection molding process - Moritzer, Elmar; Richters, Maximilian (Journal of Applied Polymer Science)

Entwicklung der Spritzniettechnik als werkstoffgerechtes Fügeverfahren für hybride Strukturen - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (11. Fügetechnisches Gemeinschaftskolloquium)

Er kommt auf die Korngröße an, Mikrogranulat verbessert die Verteilung feindisperser Füllstoffe in der Direktcompoundierung - Moritzer, Elmar; Jilg, J.; Rücker, Tobias (Kunststoffe)

Eine runde Sache - Schöppner, Volker; Martens, Jan Hendrik (Kunststoffe)